PENGARUH PROGRAM LITERASI SEKOLAH, SUPERVISI KEPALA SEKOLAH DAN KOMUNITAS BELAJAR TERHADAP PENINGKATAN KOMPETENSI GURU DI SMA SWASTA KORWIL 11 KABUPATEN BOGOR - Muhamad Rizki; Nuryati Djihadah; Neng Nurhemah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of the School Literacy Program, Principal Supervision, and Learning Community on Teacher Competency Improvement in Private Senior High Schools of Regional Coordinator (Korwil) 11, Bogor Regency, both partially and simultaneously. The study employed a quantitative approach with an associative research design. The population consisted of 370 teachers, with a sample of 192 teachers selected through probability sampling. Data were collected using a Likert-scale questionnaire that had met validity and reliability requirements. Data analysis was conducted using descriptive and inferential statistics with SPSS, including Pearson Product-Moment correlation analysis and the coefficient of determination. The findings indicate that the School Literacy Program has a positive effect on Teacher Competency Improvement with a correlation coefficient of 0.531 and a contribution of 53.1%. Principal Supervision also has a positive effect with a correlation coefficient of 0.551 and a contribution of 55.1%, while the Learning Community contributes positively by 11.5%. Simultaneously, the School Literacy Program, Principal Supervision, and Learning Community demonstrate a strong positive relationship with Teacher Competency Improvement, with a correlation coefficient of 0.716 and a combined contribution of 71.6%. These findings suggest that improving teacher competency can be effectively achieved through strengthening school literacy programs, implementing effective principal supervision, and fostering sustainable learning communities.